2010
DOI: 10.1016/s1028-4559(10)60098-8
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Reciprocal Translocations Detected at Amniocentesis

Abstract: Balanced reciprocal translocations detected at amniocentesis may be associated with fetal anomalies in cases of concomitant aneuploidy, de novo X-autosome translocation or de novo CCR. Genetic counseling of a de novo simple reciprocal translocation at amniocentesis remains difficult because approximately one-fourth of the parents opt for termination of the pregnancy, and detailed ultrasonography and array comparative genomic hybridization are helpful for parental counseling under such circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
2
13
1
1
Order By: Relevance
“…All children were delivered at term with normal birth parameters, a finding that is consistent with the normal birth measurement data previously described . The 6% rate of congenital anomalies detected at birth also appears to be consistent with the rate reported for de novo ABCRs in the literature (6–7%) . The 2/64 (3%) stillbirth rate appears similar to the 4/291 (1.4%) rate reported by Warburton (1991); however, only two neonatal deaths were reported in Warburton's study, and none reported in other studies .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All children were delivered at term with normal birth parameters, a finding that is consistent with the normal birth measurement data previously described . The 6% rate of congenital anomalies detected at birth also appears to be consistent with the rate reported for de novo ABCRs in the literature (6–7%) . The 2/64 (3%) stillbirth rate appears similar to the 4/291 (1.4%) rate reported by Warburton (1991); however, only two neonatal deaths were reported in Warburton's study, and none reported in other studies .…”
Section: Discussionsupporting
confidence: 89%
“…This risk of a phenotypic abnormality means that prenatal counselling for couples whose foetus has been identified as having a de novo ABCR is difficult; although there is a risk that the child could have an adverse outcome, information regarding the likelihood of an abnormal phenotype and the type of abnormalities seen in association with a de novo ABCR is limited. On the basis of short‐term follow‐up data, the reported risks of congenital abnormalities in prenatally detected de novo ABCRs vary from 6.1 to 12.5% …”
Section: Introductionmentioning
confidence: 99%
“…Balanced translocations; It has been accepted that familial balanced translocations detected by prenatal diagnosis are not associated with phenotypical abnormalities (9). However, in 6% of the prenatally detected de novo balanced reciprocal translocations have been associated with a risk We detected eight supernumerary marker chromosomes in our cohort with a frequency of 0.079%.…”
Section: Resultsmentioning
confidence: 54%
“…The prenatal detection of apparently balanced, de novo chromosome rearrangements by conventional cytogenetic techniques should necessarily be followed up with microarray analysis to evaluate the possibility of an imbalance 5 . Chromosomal microarray is now a recommended fist tier clinical test for the evaluation of individuals with developmental delay or congenital anomalies 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, approximately 40% of patients with a clinical phenotype and an apparently balanced translocation by conventional cytogenetics have been shown, by chromosome microarray, to carry a cryptic imbalance that would be consistent with their clinical phenotype 4 . In prenatal diagnosis, therefore, chromosome microarray diagnosis is recommended for fetuses with a de novo chromosome rearrangement 5 . We report an apparently balanced, de novo translocation detected prenatally by conventional karyotype in a patient with epilepsy and neurodevelopmental dysfunction of unknown etiology.…”
mentioning
confidence: 99%